The Effect of Pilates Stable Device with Instability Device Using the Circuit Training Method on Balance, Flexibility, and Abdominal Muscle Strength - Risfandi SETYAWAN; Hari SETIJONO; Nining Widyah KUSNANIK (Editura Universităţii din Oradea, 2021)
The purpose of this study was to analyze the effect of a stable device with an instability device using circuit training method on balance, flexibility, abdominal muscle strength. This research used quasi-experimental design by giving exercises aided instability devices using a gym ball with a circuit training method in six training posts. Trainer used the gym ball instability devices programmed: 1) bridge on stability ball, 2) single leg on stability ball, 3) hip lift on stability ball, 4) single-leg hip lift on stability ball, 5) stability ball leg rotations stability ball leg rotations 6) prone scaption (Y) on stability ball. Total population is 90 male students, age ± 19 years, height ± 164.40 cm, and body weight ± 55.33kg. From the test of each group (paired sample), it was found that there was a significant difference between pretest and posttest on the variable group of stable devices with instability devices (p-value> 0.05), while the control group did not have any difference (p-value <0.05). Meanwhile, ANOVA test results obtained only the average value of the balance variable in the instability device group using gym ball with control (p-value 0.002 <0.05), the stable device using a mattress and control (p-value 0.000 <0.05), the flexibility group of the stable devices using a control mattress (p-value 0.001 <0.05), the abdominal muscle strength device instability using a gym ball with a control (p-value 0.007 <0.05 <0.05) which has a difference.